2015
DOI: 10.1039/c5ra18602a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cement paste reinforced by graphene oxide/carbon nanotubes composites with enhanced mechanical properties

Abstract: This paper presented the enhanced mechanical properties of cement paste reinforced by graphene oxide (GO)/carbon nanotubes (CNTs) composites. The space interlocking mechanism of the GO/CNTs/cement paste composite was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(79 citation statements)
references
References 19 publications
5
72
0
2
Order By: Relevance
“…More specifically, the GO with an extra high specific area provides a template in the AAS system so that the C-(A)-S-H gel can grow on the surface of the GO due to the cross-linking between the functional groups on the GO and the divalent ions in the gel [22]. Hence, significant reinforcement of the AAS 10 by the GO can be attributed to strong interfacial adhesion between the GO and C-(A)-S-H [41,42].…”
Section: Microstructural Investigationsmentioning
confidence: 99%
“…More specifically, the GO with an extra high specific area provides a template in the AAS system so that the C-(A)-S-H gel can grow on the surface of the GO due to the cross-linking between the functional groups on the GO and the divalent ions in the gel [22]. Hence, significant reinforcement of the AAS 10 by the GO can be attributed to strong interfacial adhesion between the GO and C-(A)-S-H [41,42].…”
Section: Microstructural Investigationsmentioning
confidence: 99%
“…Due to its good dispersity in water, high aspect ratio and satisfied mechanical properties, GO has become a good candidate to reinforce cementitious materials. Lu et al [16] demonstrated that 0.05 wt.% GO led to 11.1% and 16.2% increase in compressive strength and flexural strength of the cement paste. Duan et al [17] found that 0.03 wt.…”
Section: Introductionmentioning
confidence: 98%
“…However, their inherent cracks due to lesser tensile strength and strain capacity constitute a main drawback. [1][2][3][4][5][6] As we know, graphene oxide (GO) has many unique properties, such as excellent mechanical properties, high surface functionalization, high surface area and good dispersibility in aqueous solvents. Also, there contains many active groups in the GO sheet, such as carboxyl group (-COOH) on the edges of GO sheets, epoxy group (-CH(O)CH-) and hydroxyl group (-OH) on the basal planes.…”
Section: Introductionmentioning
confidence: 99%